PENALTY APPROXIMATIONS TO THE STATIONARY POWER-LAW NAVIER-STOKES PROBLEM - Wei, Dongming (Numerical functional analysis and optimization, 2001)
In this work, penalty approximations to the steady state Navier-Stokes problem governed by the the power-law model for viscous incompressible non-Newtonian flows in bounded convex domains in R d (2 ≤ d) are studied. Existence and uniqueness of solutions to the penalty approximations are proved, convergence is shown, and rates of convergence are derived.